(3eHGOF Yde GdEMUGA GdhUaj hGdJMdjdjs - (3GHQGgje Ydi GHQGgje(B, (3YHO QHgs ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3ebOeI hJYGQja(B-(3LeY GdHjGfGJ hGdeYdheGJ GdEMUGFjI(B-(3JUfja hYQV GdHjGfGJ GdEMUGFjI(B-(3JMdjd GdHjGfGJ GdEMUGFjI(B-(3ebGjjS GdJTJJ(B-(3GdEdJRGe hGdYRhe(B-(3OQGSI GdYdGbI Hjf eJZjQjf Ch CcKQ(B-(3GdCQbGe GdbjGSjI(B-(3GdSdGSd GdRefjI(B-(3ebOeI aj fXQjI GdEMJeGdGJ hGdJhRjYGJ(B-(3GdJhRjYGJ GdEMJeGdjI dHYV GdeJZjQGJ GdefaUdI hGdeJUdIs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA Gdcejs; (3GdEMUGA GdhUajs